L-tryptophan production by Escherichia coli in the presence of Iranian cane molasses - Dehghan Shasaltaneh, Marzieh; Fooladi, Jamshid; Moosavi-Nejad, Seyedeh Zahra (Archives of Advances in Biosciences, 2010)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:1; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 0 0 0 0 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0in; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> The essential amino acid L-tryptophan (Trp) has importance as a pharmaceutical agent, especially in neuro-medicine. It is also added to feed products as a food fortifier. Furthermore, application of Trp is widespread in biotechnology. Trp is produced by a condensation reaction between indole and L-serine, which is catalyzed by bacterial tryptophanase activity. In this study, we have investigated Trp production using microbial system in the presence and absence of its precursors and Iranian cane molasses. The results showed that the optimum concentration of the molasses for maximum bacterial growth is 10 g/lit. Furthermore, in order to assay the amount of tryptophan produced, thin layer chromatography was used. The results showed that Iranian cane molasses contains considerable amounts of serine and indole, enough for Trp production (0.48 mM) in culture medium. But additional indole has inhibitory effects on Trp production. The data are compatible with previous reports on inhibitory effect of indole not only on cell growth but also on tryptophanase formation and function.